High specificity of Trypanosoma cruzi epimastigote ribonucleoprotein as antigen in serodiagnosis of Chagas' disease. - Solana, M E (1995)
We assessed the performance of an enzyme-linked immunosorbent assay (ELISA) with the Trypanosoma cruzi epimastigote ribosomal fraction (Tulahuen and Y strains) in order to improve the diagnostic specificity of the test. A total of 100 serum samples from patients with chronic Chagas' disease from Brazil and Argentina were studied. Sera from 116 patients, without Chagas' disease, including 10 with active mucocutaneous leishmaniasis and 20 with visceral leishmaniasis, were used as controls. Immunoglobulin G (IgG) antibodies against the ribosomal fraction (ribonucleoproteins [RNPs]) in the ELISA were found in 97% of samples from patients with Chagas' disease. A total of 99% of the sera from patients without the disease were negative, including sera from patients with mucocutaneous and visceral leishmaniases. The distribution of IgG isotypes in randomly chosen serum samples was determined by ELISA; IgG1 and IgG3 were predominant (100% exhibited IgG1 and 85% exhibited IgG3, and 50% also presented the IgG2 isotype. The distribution of the IgG subclasses was confirmed by the Western blot (immunoblot) technique. When total IgG was assayed by Western blot assay, no correlation was found between the pattern of serum reactivity and the clinical features of the patients with Chagas' disease. Therefore, no typical profile of polypeptide recognition could be associated with any clinical form of Chagas' disease (cardiomyopathy or megaviscera). Our results showed that sera from patients with Chagas' disease react with ribosomal antigens and display a typical profile of IgG isotypes (IgG1 plus IgG3).(ABSTRACT TRUNCATED AT 250 WORDS)